2017
DOI: 10.1007/s11044-017-9602-7
|View full text |Cite
|
Sign up to set email alerts
|

Walking of biped with passive exoskeleton: evaluation of energy consumption

Abstract: The paper aim is to show theoretically the feasibility and efficiency of a passive exoskeleton for human walking and carrying a load. Human is modeled using a planar bipedal anthropomorphic mechanism. This mechanism consists of a trunk and two identical legs; each leg consists of a thigh, shin, and foot (massless). The exoskeleton is considered also as an anthropomorphic mechanism. The shape and the degrees of freedom of the exoskeleton are identical to the biped (to human) -the topology of the exoskeleton is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Then, by using equations (A.2) and (A.3) we can recover (26) and finally (27) as follows where it is shown that…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, by using equations (A.2) and (A.3) we can recover (26) and finally (27) as follows where it is shown that…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Unlike the two previous cases where a desired fix position of the ZMP was chosen, in here it is proposed to define a trajectory for the ZMP while the robot perform a step. Several studies about the evolution of ZMP on a human walking gait, such as [25,26,27] can be used with the essential model in order to develop human-like walking gaits.…”
Section: The Desired Motion Of the Zmpmentioning
confidence: 99%
“…This step is defined by a phase of single support and an impact with the ground. The impact model is the same used in [3]. We assume that trajectories describing the motion are defined by polynomial functions of fourth order, depending on time.…”
Section: Geometric and Kinematic Conditionsmentioning
confidence: 99%
“…This step is defined by a phase of single support and an impact with the ground. The impact model is the same used in [6]. We assume that trajectories describing the motion are defined by polynomial functions of fourth order, depending on time.…”
Section: B Definition Of the Optimal Trajectoriesmentioning
confidence: 99%